2013
DOI: 10.1016/j.ijsu.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Serratiopeptidase: A systematic review of the existing evidence

Abstract: Serratiopeptidase is being used in many clinical specialities for its anti-inflammatory, anti-edemic and analgesic effects. It is even being promoted as a health supplement to prevent cardiovascular morbidity. The existing scientific evidence for Serratiopeptidase is insufficient to support its use as an analgesic and health supplement. The data on long-term safety of this enzyme is lacking. Evidence based recommendations on the analgesic, anti-atherosclerotic efficacy, safety and tolerability of Serratiopepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 18 publications
2
46
0
13
Order By: Relevance
“…This finding confirmed the synergistic anti-inflammatory effect of metformin and serratiopeptidase. Additionally, these findings coincide with results of Kim et al [39] in South Korea and Bhagatet [17] et al study in India which clarified the anti-inflammatory effect of metformin and serratiopeptidase enzyme.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding confirmed the synergistic anti-inflammatory effect of metformin and serratiopeptidase. Additionally, these findings coincide with results of Kim et al [39] in South Korea and Bhagatet [17] et al study in India which clarified the anti-inflammatory effect of metformin and serratiopeptidase enzyme.…”
Section: Discussionsupporting
confidence: 91%
“…Reduction of weight loss was proved to improve both pain and movement in obese patients with knee OA [10]. Many pharmacological agents were used efficiently in treatment of knee OA like systemic non-steroidal anti-inflammatory drugs (NSAIDs) [11], topical creams [12], glucosamine [13], diacerein [14], plateleterich-plasma [15], metformin [16] and serratiopeptidase [17].…”
Section: Managementmentioning
confidence: 99%
“…Shivani Bhagat et al, conducted a systematic review on the evidence available for the use of serratiopeptidase. 6 They reviewed a total of 9 RCTs and concluded that the existing scientific evidence for serratiopeptidase is insufficient to support its use as an analgesic or health supplement. The data on long-term safety of this enzyme is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated for the conditions such as back pain, fibromyalgia, migraine headache, rheumatoid arthritis, tension headache, osteoporosis, osteoarthritis, carpal tunnel syndrome, laryngitis, sinusitis, pharyngitis, catarrhal rhinopharyngitis, tonsillitis, chronic bronchitis, bronchial asthma, chronic obstructive pulmonary disease, Crohn's disease, ear infections, ulcerative colitis, heart disease, leg ulcers, autoimmune diseases, psoriasis, allergies, keratitis, uveitis, endophthalmitis, subconjunctival hemorrhage, hyphemas, vitreous hemorrhage, infections, diabetes, atherosclerosis, facial swelling, fibrocystic breast disease, cystitis, epididymitis, episiotomy, hysterectomy, thrombophlebitis, hematomas, septic abortion, pelvic inflammatory disease, salpingitis, sprains and torn ligaments, lacerations, and other traumatic injuries, edema, as well as postoperative inflammation [31,32].…”
Section: General Usesmentioning
confidence: 99%
“…Although the clinical efficacy and safety of serratiopeptidase has been proven in many studies, most of the evidence is based on animal experiments, few uncontrolled clinical trials, and randomized controlled clinical trials of poor quality. Thus, there is a need for further extensive experimental and clinical research in this area [30,31,[58][59][60].…”
Section: Kumarmentioning
confidence: 99%